Senam Kaki Meningkatkan Kelembaban Kulit Kaki pada Diabetisi - I Wayan Sukawana; I Made Sukarja; Ni Made Wedri (Jurnal Gema Keperawatan, 2016)
The purposes of this research were to know the influence of foot gymnastics toward skin moisture on the feet. The method of the research is “Quasy Experiment” with Pre-posttest design without control group each 13 sample was taken by simple random. Skin moisture feet before foot gymnastics = 27.91 % ± 6.28 and after foot gymnastics for six month = 36.04 % ± 8.70. The paired t test can be concluded that foot gymnastics can increase skin moisture on the feet of patients with diabetes mellitus.